Bulk chemical compositions of Antarctic meteorites in the NIPR collection - Kimura, M.; Imae, N.; Yamaguchi, A.; Haramura, H.; Kojima, H. (Polar Science, 2018)
Bulk chemical compositions of meteorites were traditionally analyzed by wet chemical analysis, and NIPR has data for 1162 meteorites as of September 2017. We discuss the classification of meteorites on the basis of these data. Chondrite data are distributed in an anomalously wide range of compositions on the Urey-Craig diagram. One of the reasons for such wide distribution is terrestrial weathering producing Fe2O3–bearing phases from Fe-Ni metal and sulfides. Another important factor affecting the bulk compositional data is brecciation. Our observations indicate that many brecciated chondrites contain anomalously abundant opaque minerals, or are depleted in them, resulting in unusual compositions. In case of enstatite and some carbonaceous chondrites, the bulk compositions are distributed in wider ranges than reported before. The bulk compositions of HED meteorites are consistent with their mineralogy and classification. Our study suggests that wet chemical data are still significant for the meteorite classification. However, petrographic observation is indispensable for evaluating the bulk chemistry and classification of meteorites. 国立極地研究所は1162個の隕石の全岩化学組成を湿式分析法により得た。本論文ではこのデータを基に隕石の分類を検討した。コンドライトをユーレイ—クレイグ図にプロットすると異常な領域に分布するものが認められる。地球上での風化作用が一因である。また角礫岩化作用の寄与も大きい。光学顕微鏡観察によれば異常な組成の普通コンドライトの多くは角礫岩である。エンスタタイト・コンドライトや炭素質コンドライトでは従来のデータより広い範囲の全岩化学組成を持つことが明らかになった。HED隕石の全岩化学組成は鉱物組合せや分類と一致する。本研究により湿式分析法による全岩化学組成データは分類上、重要であることがわかった。これと同時に全岩化学組成や分類の議論に当たっては岩石学的観察が不可欠であることも示した。 journal article